The Impact of Resource Allocation on the Machine Learning Lifecycle - Sebastian Duda; Peter Hofmann; Nils Urbach; Fabiane Völter; Amelie Zwickel (Business & Information Systems Engineering, 2023)
An organization's ability to develop Machine Learning (ML) applications depends on its available resource base. Without awareness and understanding of all relevant resources as well as their impact on the ML lifecycle, we risk inefficient allocations as well as missing monopolization tendencies. To counteract these risks, the study develops a framework that interweaves the relevant resources with the procedural and technical dependencies within the ML lifecycle. To rigorously develop and evaluate this framework the paper follows the Design Science Research paradigm and builds on a literature review and an interview study. In doing so, it bridges the gap between the software engineering and management perspective to advance the ML management discourse. The results extend the literature by introducing not yet discussed but relevant resources, describing six direct and indirect effects of resources on the ML lifecycle, and revealing the resources' contextual properties. Furthermore, the framework is useful in practice to support organizational decision-making and contextualize monopolization tendencies.
Keywords: 000; ML management; Machine learning lifecycle; Artificial intelligence; Resource-based view; Design science research